“If I fall down, he will pick me up”: refugee hosts and everyday care in protracted displacement - Jordan, Zoe (Frontiers in Human Dynamics, 2024)
Around the world, refugees share shelters and homes with other refugees. Such household-level hosting relationships play a central role in the lives of displaced individuals and families, offering support to meet basic needs, safety, and a sense of belonging. Yet, the role of displaced people as refugee hosts is often overlooked, an omission that fails to account for the active role of displaced populations in supporting one another and the dynamic social connections between refugees.Thus far, hosting relationships have often been understood through hospitality. Instead, in this paper I develop an understanding of refugee-refugee hosting as constituted through care. Drawing on qualitative research conducted with Sudanese refugee men in Amman, Jordan, I demonstrate the value of this framework in explaining the emergence and experiences of their hosting relationships. I highlight the importance of everyday interdependencies for life in displacement, alongside the challenges and ambivalences of providing and receiving care in such contexts, and show how configurations of care shift and alter throughout protracted displacement. In doing so, I centre informal and everyday acts of care among refugees in relation to external humanitarian care, arguing for a re-conceptualisation of the relationship between 'hosts' and 'humanitarians', and propose avenues for those working with displaced populations to engage with the vital support that refugeerefugee hosting provides.